Beyond Empathy: Teaching Alterity - Burcher, Paul (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
Clinical empathy has been increasingly recognized as an important component of both professionalism and good patient care. It is generally understood as identifying commonality between patient and provider and responding to this shared experience with appropriate care and concern. However, many clinical encounters are between strangers with little shared experience, which seems to present a challenge for both empathy and a sense of responsibility toward the patient. Physicians can also develop a deep sense of caring and responsibility by learning to appreciate the alterity, the otherness, of the patient, and this skill, like clinical empathy can be modeled and taught. Philosopher Emmanuel Levinas described respect for alterity as foundational to human relationships. That is, my primary experience in meeting other people is one of difference, not an immediate sense of similarity. This sense of difference is both superficial and profound, although in most cases we will recognize only the superficial. Recognizing the profundity of difference opens one up to a radical sense of alterity that is the source of ethics, including our responsibility to the other. By exploring Levinas’ descriptions of human responsibility, humans as infinite and unique, and the consequences of this philosophy for the clinical encounter, it is evident that respect for alterity represents an underappreciated source of human caring, accessible in clinical relationships, even between a patient and physician with radically different life experiences. The implications of this for medical education are that we must help students appreciate and respect both the commonality we share with our patients, and the differences that makes them special and worthy of our care and attention.